Analisis Pengaruh Sosial Media Instagram Terhadap Minat Beli Konsumen - Ahmad Jaelani; Apid Hapid Maksum (Jurnal Ilmiah Wahana Pendidikan, 2022)
Purchase intention is one of the first things that consumers consider when making a purchase. From the logistics side, good social media management encourages consumers to buy products. Based on this problem, where the use of Instagram can attract Baka Sport consumers. where the use of Instagram can be effective or not on buying interest. The method in this research uses a quantitative method with a descriptive approach that is adapted to the objectives and research variables. This study aims to identify or find out how the influence of social media Instagram on consumer buying interest in Baka Sport. From the results of data processing obtained a correlation coefficient of 0.493 and can be classified as having a strong influence on the purchase motivation of the Instagram variable. In addition, the coefficient of determination is obtained: R2 24.3%. R2 is a number that shows the magnitude of the influence of variable X on variable Y. Descriptively the effect of X on Y is 24.3 with the rest being the influence of other factors besides social media. The results of analysis and interpretation of research data on Instagram social media variables show that photo communication with text creatively packaged is one of the most important factors to attract consumers' attention to increase consumer interest in Baka Sport. The social networking application Instagram has an image or photo sharing feature that is proven to be strongly correlated to influence consumer buying preferences